Homelessness and mental health - Bhugra, Dinesh (Cambridge University Press, 1996)
As homelessness becomes an increasingly visible problem, the health care of homeless people is beginning to appear on the agenda of politicians, health care workers, and policy makers. In contrast with the popular stereotype of elderly alcoholic males or bag ladies which the word homeless tends to trigger, homelessness affects families as well as young single people. The health needs of these various groups are not homogeneous. This book brings together the experience of mental health care teams around the world in addressing the problems of mental illness in the homeless. The difficulties in assessment and service delivery are discussed at length with an emphasis on application of existing knowledge in health care. In addressing social policy implications as well as clinical management, models, and definitions of homelessness in different cultures, this volume will offer a practical support for all those working with the homeless on a day-to-day basis
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Homeless persons / Mental health; Homeless persons / Mental health services; Psychiatrische Versorgung; Psychische Störung; Nichtsesshaftigkeit; Aufsatzsammlung